2020
DOI: 10.1038/s41377-020-00438-w
|View full text |Cite
|
Sign up to set email alerts
|

Dirac solitons in optical microresonators

Abstract: Mode-coupling-induced dispersion has been used to engineer microresonators for soliton generation at the edge of the visible band. Here, we show that the optical soliton formed in this way is analogous to optical Bragg solitons and, more generally, to the Dirac soliton in quantum field theory. This optical Dirac soliton is studied theoretically, and a closed-form solution is derived in the corresponding conservative system. Both analytical and numerical solutions show unusual properties, such as polarization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 73 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…1a. This peculiar effect is also associated with Dirac solitons [16] and it is shown that the 2-ring pulse pair represents a new embodiment of a Dirac soliton as the underlying dynamical equation (see Methods) resembles the nonlinear Dirac equation in 1 + 1 dimensions. Pulse pairing is also extendable to higher-dimensional designs with additional normal dispersion rings.…”
Section: Introductionmentioning
confidence: 85%
“…1a. This peculiar effect is also associated with Dirac solitons [16] and it is shown that the 2-ring pulse pair represents a new embodiment of a Dirac soliton as the underlying dynamical equation (see Methods) resembles the nonlinear Dirac equation in 1 + 1 dimensions. Pulse pairing is also extendable to higher-dimensional designs with additional normal dispersion rings.…”
Section: Introductionmentioning
confidence: 85%
“…Dirac solitons are generated by engineering dispersion induced by nonlinear modecoupling in the visible band [166]. They normally have asymmetric soliton comb spectra due to different mode compositions on the different sides of the spectra.…”
Section: Soliton Classesmentioning
confidence: 99%
“…This localized dispersion perturbation can lead to a local anomalous dispersion which can meet a phase-matching condition for the four wave mixing (FWM) process. At visible or near visible wavelengths, optical frequency combs have been generated via AMXs in a crystalline WGM resonator [30], a microring resonator [32][33][34], dual microring resonators [35,36], and a wedge disk resonator [37][38][39]. Chip-based ring resonators can be designed to introduce AMXs at desired locations using a thermal heater [40] or by adding an another resonator nearby [35,36,41].…”
Section: Dispersion Engineering and Avoided Mode Crossingsmentioning
confidence: 99%